A Switching Method for Improving Lifetime of DC-Link Capacitors in Hybrid ANPC Inverters - Kim, Ye Ji; Kim, Seok Min; Lee, Kyo Beum (2019 IEEE Student Conference on Electric Machines and Systems, SCEMS 2019, 2019)
This paper presents a switching strategy for improving lifetime of DC-link capacitors in photovoltaic (PV) hybrid active neutral-point-clamped (ANPC) inverters. The DC-link capacitor current ripples should be reduced, because the high current ripples of the capacitors cause high thermal stress and short lifetime of the capacitors. To reduce the DC-link current ripples, the switching sequence of the conventional space vector pulse width modulation (SVPWM) method is replaced with the proposed switching sequence. By applying the proposed method, the DC-link current ripples are reduced substantially. The effectiveness of the proposed method was verified by simulation results.
Keywords: Active neutral point clamped; Current ripples; Dc link capacitor; Dc link currents; Space vector pulse width modulation; Switching methods; Switching sequence; Switching strategies; current ripple; DC-link capacitor; hybrid active neutral-point-clamped; reliability; switching strategy